1940
DOI: 10.1113/jphysiol.1940.sp003841
|View full text |Cite
|
Sign up to set email alerts
|

Discharges from the sensory organs of the cat's vibrissae and the modification in their activity by ions

Abstract: RECORDS from the cutaneous nerves of the cat, rabbit and guinea-pig [Adrian & Zotterman, 1926;Zotterman, 1939] have given information as to the sensory discharges from the hairs covering the body surface. These discharges are usually of brief duration, occurring only when movement is carried out and ceasing when a steady deflected position is reached. The nerve endings stimulated by hair movement can therefore be described as rapidly adapting, although the short duration of the discharges might be due to mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

1954
1954
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(33 citation statements)
references
References 10 publications
2
30
1
Order By: Relevance
“…Therefore, differences in the deflection angle of the vibrissal shaft result in mechanical stimulations of different intensity inside the follicle, which then lead to a different response of the follicle receptors. It has been repeatedly shown that the discharge rate of impulses in the slowly adapting afferent fibers of the trigeminal nerve rise in proportion to the extent of the vibrissae's deflection angle (Dykes, 1975;Fitzgerald, 1940;Gottschaldt, Iggo, & Young, 1973;Hahn, 1971;Hunt & Mcintyre, 1960). When the neural mechanism underlying the size discriminations of the sea lion is the measurement of impulse rates of afferent fibers, the animal used, according to the definition by Johnson and Phillips (1981), a "purely intensive cue" for its discriminations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, differences in the deflection angle of the vibrissal shaft result in mechanical stimulations of different intensity inside the follicle, which then lead to a different response of the follicle receptors. It has been repeatedly shown that the discharge rate of impulses in the slowly adapting afferent fibers of the trigeminal nerve rise in proportion to the extent of the vibrissae's deflection angle (Dykes, 1975;Fitzgerald, 1940;Gottschaldt, Iggo, & Young, 1973;Hahn, 1971;Hunt & Mcintyre, 1960). When the neural mechanism underlying the size discriminations of the sea lion is the measurement of impulse rates of afferent fibers, the animal used, according to the definition by Johnson and Phillips (1981), a "purely intensive cue" for its discriminations.…”
Section: Discussionmentioning
confidence: 99%
“…It is of great interest that Boyd (1954) has been able to identify the 'rapidly adapting' receptor of Boyd & Roberts as an elongated lamellated corpuscle and the 'slowly adapting' receptor as a spray (or Ruffini) ending, since Lewinsky & Stewart (1936) illustrate apparently similar endings found in preparations from the periodontal membranes of cat and rabbit. Directionality A relationship between the direction of a mechanical stimulus and the response of a stimulated sensory receptor has been observed in mechanoreceptors of the lateral line organ of fish (Sand, 1937), and of the teeth (Pfaffmann, 1939a), vibrissae (Fitzgerald, 1940), and knee-joint (Boyd & Roberts, 1953) of the cat. The incisor tooth of the rabbit has provided a suitable preparation for examining this relationship in some detail.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanoreceptors discharged by movement of the vibrissae are very sensitive and slowly adapting when subjected to a constant stimulus (cf. Fitzgerald, 1940). The vibrissae are often very long and reach in front of the cat's nose.…”
Section: Discussionmentioning
confidence: 99%